Peripheral Blood Markers Identify Risk of Immune‐Related Toxicity in Advanced Non‐Small Cell Lung Cancer Treated with Immune‐Checkpoint Inhibitors. (23rd April 2019) - Pavan, Alberto; Calvetti, Lorenzo; Dal Maso, Alessandro; Attili, Ilaria; Del Bianco, Paola; Pasello, Giulia; Guarneri, Valentina; Aprile, Giuseppe; Conte, PierFranco; Bonanno, Laura
Abstract: Background: Immune‐checkpoint inhibitors (ICIs) are now standard of care for advanced non‐small cell lung cancer (NSCLC). Unfortunately, many patients experience immune‐related adverse events (irAEs), which are usually mild and reversible, but they require timely management and may be life threatening. No predictive markers of irAEs are available. Materials and Methods: The neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) were evaluated in patients with NSCLC consecutively treated with ICIs. Prespecified cutoff values of NLR and PLR were used and related to outcome and onset of irAEs. A control group of patients with advanced NSCLC not receiving ICIs was included. Results: The study included 184 patients: 26 (14.1%) received pembrolizumab upfront, and 142 (77%) received ICIs (pembrolizumab, nivolumab or atezolizumab) after one or more lines of chemotherapy. The median number of ICIs cycles was six (range, 1–61). The median progression‐free survival and overall survival were 4.8 (95% CI, 3.4–6.3) and 20.6 (95% CI, 14.7–26.5) months, respectively. Sixty patients (32.6%) developed irAEs, mainly grade 1–2 (65.0%), causing ICI interruption in 46 cases (25.0%). Low NLR and low PLR at baseline were significantly associated with the development of irAEs (odds ratio [OR], 2.2; p = .018 and OR, 2.8; p = .003, respectively). Multivariate analyses confirmed PLR as independent predictive marker of irAEs (OR, 2.3; p = .020). Conclusion: NLR and PLR may predict the appearance of irAEs in non‐oncogene‐addicted aNSCLC, although this conclusion warrants prospective validation. Abstract : Predictive markers for immune‐related adverse events (irAEs) are not available. This article evaluates the association of peripheral blood markers with the onset of irAEs in patients with non‐oncogene addicted advanced non‐small cell lung cancer treated with immune‐checkpoint inhibitors.